338. Results of routine monitoring of internal contamination of workers in a Nuclear Medicine department. (December 2018) - Matheoud, R.; Cannillo, B.; Sacchetti, G.M.; Brambila, M.
Abstract : Purpose: Internal contamination may occur when unsealed radioactive substances are manipulated for radiopharmaceutical preparation. This work presents the result of routine monitoring of workers in a Nuclear Medicine department dealing with Tc99m, I123, I131, In111, F18, Cr51, in a 12-months period. F18 dose preparation is performed through and automatic dose partitioner. Methods: Every week, urine samples were collected from the most exposed workers to the risk of internal contamination, namely the technician (TEC) working in the hot-lab and the nuclear medicine physician (NMP) devoted to patients injection. Samples were measured for 3600 ″ with a NaI(Tl) scintillation detector, previously calibrated in efficiency. Minimum detectable activities (MDA) were: 1.0, 1.0, 1.7, 2.3, 3.6 and 13.7 Bq for Tc99m, I123, I131, In111, F18 and Cr51, respectively. The intake at the time of contamination was derived from the activity in the urine sample by using biological models in the hypothesis that the contamination happened two days before. The committed effective dose was evaluated by using ICRP coefficients for ingestion. The annual workload of manipulated activity was: 3.0, 17.0, 21.8, 0.3, 8462 GBq of Tc99m, I123, I131, In111, F18 and Cr51, respectively. Results: For the monitored period, the evaluated intakes were 1.2 10 6 (1.1 10 6 ) Bq, 2.5 10 4 (1.5 10 3 ) Bq, 1.4 10 3 (1.2 10 3 ) Bq, 3.0 10 3 (0) Bq and 1.2 10 3 (2.3 10 2 ) Bq for TEC and (NMP) respectively, and the committed effective doses of 25.3 (24.7) μSv, 5.2 (0.3) μSv, 31.5 (27.4) μSv, 0.9 (0) μSv and 0 (0) for Tc99m, I123, I131, In111 and Cr51, respectively. As expected, F18 activity in urine was below the MDA. Conclusions: The results of the routine monitoring of internal contamination shows that the committed effective dose to the workers in a Nuclear Medicine department is definitely lower than 1 mSv, showing highly safe working conditions.